A Novel Pale-Yellow Coat Color of Rabbits Generated viaMC1R Mutation With CRISPR/Cas9 System - Xiao, Ning; Li, Hongli; Shafique, Laiba; Zhao, Shanshan; Su, Xiaoping; Zhang, Yu; Cui, Kuiqing; Liu, Qingyou; Shi, Deshun (Frontiers in Genetics, 2019)
Coat color is of great importance in animal breed characteristics; it is not only a significant productive trait but also an indispensable economic trait, especially in the rabbit industry. In the present study, the relationship between melanocortin 1 receptor (MC1R) genotypes and coat color phenotypes was observed in five rabbit breeds with popular coat colors that are present in China. These breeds comprised the Lianshan black rabbit (BR), Fujian yellow rabbit (YR), New Zealand white rabbit (WR), Gray Giant rabbit (GR), and Checkered Giant rabbit (CR), which were firstly determined, and the results showed that GR had an E allele; WR, CR, and BR had a 6-bp in-frame deletion (c.281_286del6, ED allele); and YR had a 30-bp deletion (c.304_333del30 E allele). To explore the feasibility of obtaining a novel rabbit coat color through the mutation of MC1R with the CRISPR/Cas9 system, two single-guide RNAs (sgRNAs) were designed for the MC1R gene, and the editing efficiency was confirmed by injection of rabbits’ zygotes. Unlike the donor rabbits whose coat color was originally black, two novel pale-yellow-coated rabbits were generated in the founders. A total of six novel MC1R gene deletions were identified in the two founder rabbits, in which the longest deletion was more than 700 bp. The histological hematoxylin-and-eosin (H&E) staining results indicated that eumelanin amounts were absent in hair follicles of MC1R-knockout (KO) rabbits, when compared with that of donor BR. In addition, the messenger RNA (mRNA) levels of some key downstream genes in the MC1R pathway were all downregulated in MC1R-KO rabbits compared with BR and YR. These results further indicate that loss-of-function MC1R contributed to blocking the synthesis of eumelanin and created a novel pale-yellow coat color in the MC1R-KO rabbits, and gene editing technology may be a useful tool to generate novel phenotypes in rabbit breeding.